Spiders of arid lands: The Ghardaïa region (Northern Sahara) with seven new records for Algeria - Alioua, Youcef; Bosmans, Robert (Zootaxa, 2024)
The spider fauna of Algeria’s Saharan region is currently little understood, even though some information is available but it remains either very old or insufficient. This study aimed to deepen our understanding on this group of arachnids in this hyper-arid land. The study was conducted in Ghardaïa province (Northern Sahara, Algeria). Spiders were collected during 2014–2017 and 2020–2023 from various localities covering either in natural or manmade ecosystems. A set of 2037 adult spiders was captured using hand collecting and pitfall traps methods. The results of the taxonomic study revealed that Ghardaia had 70 spider species representing 21 families and 55 genera. Twenty (20) species were identified under the family Gnaphosidae, followed by 12 for Salticidae and seven for Lycosidae and Theridiidae. One genus and seven species were recorded for the first time from Algeria, of which habitus and genital parts photos were provided; two species among them are new records for Africa. The results of this study raised the number of species of spiders that are known to exist in the province of Ghardaïa from 23 to 79. Thus, many species distribution ranges in Algeria have been updated. This study established the first-ever systematic list of the spiders of Ghardaïa.